KONSTRUKSI NILAI ROMANTISME DALAM LIRIK LAGU (ANALISIS SEMIOTIKA FERDINAND DE SAUSSURE PADA LIRIK LAGU "MELUKIS SENJA") - Erlangga, Christopher Yudha; Utomo, Ichsan Widi; Anisti, Anisti (Linimasa : Jurnal Ilmu Komunikasi, 2021)
This study aims to determine the construction of romantic values ​​in song lyrics. The lyrics in the song must have the information that the composer and singer want to convey, then the information has the appropriate meaning between the song lyrics and reality. This study uses a qualitative method using the semiotic analysis method of Ferdinand de Saussure, the object is the song lyrics, and analyzed each stanza. In this analysis, the steps taken are (1) determining the symbols that represent the song lyrics of the research subject (2) writing down the indicators or physical form, namely the lyrics of the song Melukis Senja. (3) Signified, the concept of sign. (4) The next step is to look at symbols, symbol forms and symbol concepts in referential or external forms with social realists. reality. This study explains how the values ​​of romantic are formed into song lyrics and then uploaded into a song with a pitch or music so that it becomes a work that can be enjoyed. Besides that, this work also contains values, where the values ​​in this study focus on romantic